Schizorhynchia (Platyhelminthes, Rhabdocoela) from eastern Cuba, with the description of fifteen new species - Diez, Yander L.; Reygel, Patrick; Artois, Tom (Zootaxa, 2019)
We report on the schizorhynch species collected in a survey in the eastern region of Cuba. Eighteen species were identified, of which only three are known to science: Cheliplana asica, C. terminalis, and Carcharodorhynchus flavidus. The 15 new species belong to three different genera: Cheliplana (five species), Carcharodorhynchus (four species), and Schizochilus (six species). The five new species of Cheliplana (C. gibarenha sp. n., C. santiaguera sp. n., C. spuriaseminalis sp. n., C. subproximalis sp. n. and C. verrucosa sp. n.) differ from their congeners in the detailed morphology of the proboscis hooks and the atrial organs. The proboscis hooks bear a distal small hook in C. verrucosa sp. n., a feature only shared with C. paradoxa. Two of the four new species of Carcharodorhynchus (C. smilodon sp. n. and C. papillaris sp. n. ) are very similar to C. flavidus in that the toothed belts of the proboscis are not continuous. However, they clearly differ from that species and from each other in the detailed construction of the teeth and copulatory organ. Carcharodorhynchus spiniformis sp. n. and C. nativus sp. n. can also be distinguished from the other species of Carcharodorhynchus by the detailed construction of the proboscis teeth and copulatory organ. The six new species of Schizochilus here described show a spiny cirrus around a central stylet. Two species lack the distal sclerotized cap of the copulatory bulb: S. favus sp. n. and S. bueycabonensis sp. n.. All new species of Schizochilus can be distinguished from each other and their congeners by the detailed construction of the hard parts (cirrus and stylet) of the copulatory organ.